2022
DOI: 10.1167/tvst.11.8.10
|View full text |Cite
|
Sign up to set email alerts
|

Using Advanced Bioinformatics Tools to Identify Novel Therapeutic Candidates for Age-Related Macular Degeneration

Abstract: Purpose Age-related macular degeneration (AMD) is the most common cause of aging-related blindness in the developing world. Although medications can slow progressive wet AMD, currently, no drugs to treat dry-AMD are available. We use a systems or in silico biology analysis to identify chemicals and drugs approved by the Food and Drug Administration for other indications that can be used to treat and prevent AMD. Methods We queried National Center for Biotechnology Infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…This study found that of the 77,146 drugs queried, metformin was the 1st potential drug candidate for wet AMD-related genes, 13th for dry AMD-related genes, and 21st for all AMD-related genes. 21 Therefore, it may have promise as a drug candidate for the prevention of AMD and nAMD, especially as it is an food and drug administration (FDA)-approved treatment for Type 2 diabetes and has few side effects. 20 In addition, it has been used safely without causing hypoglycemia and offers a similarly favorable safety profile in the treatment of other conditions, including polycystic ovarian syndrome, prediabetes, and obesity, and is being studied in others, including cardiovascular disease, malignancy, and age-related dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that of the 77,146 drugs queried, metformin was the 1st potential drug candidate for wet AMD-related genes, 13th for dry AMD-related genes, and 21st for all AMD-related genes. 21 Therefore, it may have promise as a drug candidate for the prevention of AMD and nAMD, especially as it is an food and drug administration (FDA)-approved treatment for Type 2 diabetes and has few side effects. 20 In addition, it has been used safely without causing hypoglycemia and offers a similarly favorable safety profile in the treatment of other conditions, including polycystic ovarian syndrome, prediabetes, and obesity, and is being studied in others, including cardiovascular disease, malignancy, and age-related dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Nadeem et al 82 used advanced bioinformatics modeling to identify drug classes that affect the genes integral to AMD pathogenesis. This was the first time a systems medicine approach was used to predict drugs for AMD treatment.…”
Section: Bioinformatics Tools To Support Repurposing Medicationsmentioning
confidence: 99%
“…Indeed gene product networks and gene interactions powerfully impact disease initiation and progression, and finding suitable loci and nodes for therapeutic intervention will always present new opportunities and challenges. Using such bioinformatic nodes and network analyses information, as has been deployed for dry AMD and IRDs [ 99 , 100 ] to unearth novel and repositioning of existing drugs, researchers are sure to make meaningful discoveries for the treatment of OHT/POAG over the next few years. Potential interactions of the several genes discussed above and their relationship to OHT have been presented in a pictorial manner [ 97 ], and novel pathways and components have been discussed [ 25 ].…”
Section: Poag and Gene Therapymentioning
confidence: 99%